Estimação do hiato do produto a partir da metodologia de Enders e Li (2015) - Cardoso, Monise De Jesus [UNIFESP] (2019)
This work proposes to estimate the output gap for the Brazilian and United States (US) economies. The methodology used is the Flexible Fourier Form proposed by Enders and Li (2015). The analysis period is from the first quarter of 1996 to the first quarter of 2019 for Brazil and from 1947 to 2018 for the US. Model estimates for the US are similar to those of the study by Enders and Li (2015) adding five years of observations. But pseudo real-time output gap estimates indicate instability compared to the case with the full sample. In the Brazilian case, output gap estimates are erratic, which leads to discussion about practical use for policy-maker.